Tinjauan Maqāṣid Syarī‘ah Terhadap Hukum Konsumsi Pil Diet Tanpa Resep Dokter: A Review of Maqāṣid Syarī'ah Regarding the Legality of Consuming Diet Pills Without a Doctor's Prescription (AL-FIKRAH: Jurnal Kajian Islam, 2025)
Khaṭā’ Divorce is a form of divorce pronounced by a husband to his wife unintentionally, due to a mistake in speech, being in a state of impaired consciousness, or because of certain circumstances that affect his will and awareness. In other words, khaṭā’ divorce occurs as a result of an error, inadvertence, or unintentionality whether in the utterance or in the intention to pronounce the divorce. This study examines the legal status of khaṭā’ divorce according to the Hanafi and Shafi’i schools of thought and provides a comparative analysis between their respective views, using the methodological approaches of both schools. This type of divorce has sparked differences of opinion among scholars, especially regarding the validity of a divorce uttered unintentionally or without a clear intention. This research employs a normative qualitative method through a literature review of classical and contemporary sources of Islamic jurisprudence, applying a comparative approach to analyze the differing perspectives of the two schools. The objectives are: first, to explain the Hanafi view on khaṭā’ divorce; second, to explain the Shafi’i view on khaṭā’ divorce; and third, to compare the differing opinions of both schools. The results of the study indicate that the Hanafi school deems the divorce valid as long as it is pronounced with a clear (ṣarīḥ) utterance, without considering the intention, emphasizing legal certainty. In contrast, the Shafi’i school requires intention and full awareness as essential elements, thus regarding a divorce without conscious intent as invalid. This difference reflects contrasting approaches: the Hanafi’s formalistic and textual approach versus the Shafi’i’s substantive and ethical approach. In the context of family law in Indonesia, the Shafi’i approach is considered more applicable and solution-oriented as it takes into account psychological aspects and family protection. The implications of this research contribute to the development of comparative jurisprudence and offer a foundation for contemporary ijtihād in handling cases of unintentional divorce